The Effect of Board Characteristics on Environmental, Social, and Governance (ESG) Disclosure - Nadia Triwahyuni; Aria Farah Mita (Universitas Pasundan, 2024)
This study investigates the effect of supervisory board characteristics on Environmental, Social, and Governance (ESG) disclosure in ASEAN-5 countries from 2014-2018. It explores one-tier and two-tier governance systems, where non-executive directors and commissioners perform oversight functions. The analysis focuses on board diversity, comprising female, independent, community influential, foreign, and interlock members. This study used a purposive sampling technique in sampling and obtained a sample of 115 companies with a total of 575 observational data. The findings reveal that female, community influential, and interlock board members positively influence ESG disclosure, supporting their critical role in advancing sustainability practices. Conversely, independent and foreign board members do not significantly affect ESG disclosure, highlighting potential misalignments between regulatory frameworks and practical governance outcomes in the ASEAN-5 context. The study provides insights into how diverse board characteristics contribute to ESG transparency, grounded in agency, feminism, and institutional theories. It underscores the importance of fostering board diversity and tailoring governance practices to local corporate and regulatory environments. However, limitations related to country-specific characteristics and inconsistent ESG reporting suggest avenues for future research. This study contributes to sustainability accounting literature by linking board diversity to ESG disclosure and offering recommendations for corporate governance reforms in emerging markets.